Changes in the Body of a Pregnant Woman as a Result of Hyperthyroidism - Bekzod qizi, Abduganiyeva Malika; Siddikovna, Togayeva Gulnora (American Journal of Bioscience and Clinical Integrity, 2026)
Pregnancy with hyperthyroidism is a major clinical endocrine disorder, which seriously affects the physiological state and development of the mother and fetus. Sustained overproduction of thyroid hormone changes metabolic, cardiovascular, thermal and immune response function, adding maladaptive traits to the normal physiologic responses characteristic of pregnancy. Given that pregnancy by itself causes a significant hormonal and hemodynamic modification, differentiating between abnormal hyperthyroidism and gestational thyroid fluctuations can be difficult for the physician. This article reviews the systemic changes in a pregnant patient with hyperthyroidism, specifically the metabolic, cardiovascular ,hematologic, and obstetric outcomes. Emphasis is given to pathophysiological mechanisms, maternal–foetal interactions, and clinical implications for observation and management. Understanding these physiological adaptations is crucial for preventing adverse outcomes such as preeclampsia, preterm delivery, fetal growth restriction and neonatal thyroid dysfunction. Hyperthyroidism in pregnancy is characterized by dramatic changes in metabolism, cardiovascular and endocrine function, all potentially affecting the health of both mother and fetus. Excessive thyroid hormone overstimulates resting metabolic activity, heart work and nutrients utilization as it adds to the normal physiological states of gestation. There is evidence that untreated or suboptimally treated hyperthyroidism leads to adverse obstetric outcomes such as miscarriage, preterm birth, and low-birth-weight newborns and that the infants have an increased incidence of neonatal thyroid dysfunction. This review compiles the current knowledge on systemic manifestations of maternal hyperthyroidism, focusing on mechanisms underlying metabolic alterations, cardiac stress and immune modulation. In the following we focus on clinical management and intervention measures directed at reducing maternal and fetal risks.